Dominus Tonans: the voice and light of Christianity's tempestuous god in Late Antiquity and the Middle Ages. Issue 4 (2nd October 2019) - Loic, Erika
Abstract: Late Antique Christian poets preserved the epithet tonans (thundering), one of the many descriptive terms for Jupiter, and applied it to the Christian god as a means of proclaiming his supremacy. As this poetic tradition continued into the Middle Ages, tonans and its derivatives appeared in new contexts, with the Jovian epithet and other storm-related imagery appearing in ritual environments and on precious objects. Although the classical origins and subversive connotations of the epithet receded from view, its ability to evoke lightning, thunder, and other celestial manifestations meant that it could intensify the multisensory experiences of readers and viewers. This is particularly clear when written references to the Thunderer are paired with other classical allusions, with descriptions of powerful voices and miraculous weather phenomena, or with comparisons of material brilliance and spiritual illumination. Many of these same references were designed to help audiences recall the scriptural accounts of God's celestial throne or the Ark of the Covenant revealed in Heaven. Creative uses of tempestuous symbolism also allowed artists and authors to emphasize connections among biblical motifs and to imbue text and image with apocalyptic overtones.